2020
DOI: 10.4013/cld.2020.183.15
|View full text |Cite
|
Sign up to set email alerts
|

Identity and investment in language education: an interview with Bonny Norton

Abstract: Her research interests are related to identity, power, and language learning. Her work has influenced not only us Brazilian researchers and language educators, but professionals involved with education worldwide. Her efforts to bring social justice and fight inequality through her research findings are endless, specially calling out attention to relevant issues as gender, ethnic and social class differences. Norton is a highly productive scholar, her publications include 5 books, 4 journal special issues, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
1
7
0
3
Order By: Relevance
“…In accordance with Norton [3], the study found that participants were inclined to invest more positively in prewriting activities when they perceived a gain in symbolic resources. Norton and Toohey [8] describe these resources as language skills, social networks, and educational access.…”
Section: Perceptions Of Symbolic Resourcessupporting
confidence: 69%
See 4 more Smart Citations
“…In accordance with Norton [3], the study found that participants were inclined to invest more positively in prewriting activities when they perceived a gain in symbolic resources. Norton and Toohey [8] describe these resources as language skills, social networks, and educational access.…”
Section: Perceptions Of Symbolic Resourcessupporting
confidence: 69%
“…(Eric's interview, 25 May 2023) This shift from a passive approach to actively choosing words and organizing ideas indicated a more engaged relationship between Eric and his prewriting tasks. More specifically, Eric's reconfiguration of his connection to the practices of specific prewriting discussions [3] was ostensibly driven by the pursuit of better grades. Essentially, such an investment aimed at securing the symbolic resource associated with gaining access to graduate education.…”
Section: Eric's Perspectivementioning
confidence: 99%
See 3 more Smart Citations